Polyaniline Supported Ag-Doped ZnO Nanocomposite: Synthesis, Characterization, and Kinetics Study for Photocatalytic Degradation of Malachite Green - Fikradis Habtamu; Sintayehu Berhanu; Teshome Mender (Journal of Chemistry)
Ag-ZnO/PANI nanocomposite was prepared via the sol-gel technique following in situ oxidative polymerization of polyaniline (PANI). XRD, UV-Vis, and FT-IR spectroscopy were employed to study the crystal size, bandgap energy, and bond structure of as-synthesized nanocomposites. The mean crystallite size of the nanocomposite determined from XRD was 35.68 nm. Photocatalytic degradation of malachite green (MG) dye using as-synthesized photocatalysts was studied under visible light irradiation. The highest degradation efficiency was recorded for Ag-ZnO/PANI nanocomposites (98.58%) than Ag-ZnO nanoparticles (88.23%) in 120 min. The kinetics of photocatalytic degradation of MG follows pseudo-first-order reaction with rate order of 1.16 10−2 min−1. Moreover, the photocatalytic activity of Ag-ZnO/PANI nanocomposites was evaluated and compared with Ce-Cd oxide, electrospun P(3HB)-TiO2, and with other catalysts in the literature. The optimal conditions for photocatalytic degradation are as follows: the concentration of malachite green (0.2 g/l), pH (8), and the concentration of catalyst load (0.2 g/l) under visible light with an irradiation time of 120 min.